Модель формування медіакомпетентності майбутніх лікарів у процесі доклінічної професійної підготовки в медичному університеті - Мурзіна, Олена Анатоліївна; Murzina, O. A. (My University, 2024)
У статті теоретично обґрунтовано та розроблено модель формування медіакомпетентності майбутніх лікарів у процесі доклінічної професійної підготовки в медичному університеті, розкрито сутність понять “модель” і “моделювання”. Визначення суті та структури медіакомпетентності майбутніх лікарів, аналіз дослідження їхньої медіакомпетентності, врахування особливостей соціуму та чинників, які впливають на її формування у процесі доклінічної професійної підготовки в медичному університеті дали змогу змоделювати педагогічний процес і структурувати його за етапами (теоретико-методологічний, змістовно-процесуальний, критеріально-результативний). The article theoretically substantiates and develops the model for the formation of media competence of future doctors in the process of preclinical professional training at the medical university, the meaning of the concepts “model” and “modeling” is revealed. In this research, it is modelled the pedagogical process and its structure by stages (theoretical-methodological, content-procedural, criterion-resultative) taking into account the content and the structure of the media competence of future doctors, study analysis of their media competence, the society peculiarities and the factors that influence media competence formation in the process of preclinical professional training at the medical university. The theoretical and methodological part reflects the main idea of the content and the main points outlined by the implementation program that provides a more productive approach to understanding the content and contributes to the formation of a certain type of thinking among future doctors. The main principles of training of future doctors and the structure of a doctor’s media competence are presented, the main approaches to the formation of media competence of future doctors in the process of preclinical professional training are considered. The content-procedural part reflects the psychological-pedagogical conditions and media environment of the university, it reveals and illustrates ways to solve the problem, demonstrates the process of given transformations, including classroom and extracurricular work, forms, methods, technologies and means of their implementation. The criterion-resultative part describes the monitoring of the level of formation of media competence of future doctors in the process of preclinical professional training at the medical university. It gives the analysis of research and experiment and represents relations of goals and tasks based on the results of the experiment. It states the range of problems that require further research. The proposed model is designed to ensure the continuity of the system process of forming media competence of future doctors in the process of preclinical professional training at the medical university.
The model of formation of media competence of future doctors in the process of preclinical professional training at the medical university
Keywords: модель; моделювання; медіа компетентність; медіакомпетентність лікаря; доклінічна професійна підготовка; model; modeling; media competence; doctor’s media competence; preclinical professional training